Expression of serotonin 5-HT(2A) receptors in the human cerebellum and alterations in schizophrenia. - Eastwood, S; Burnet, P; Gittins, R; Baker, K; Harrison, P (2001)
The occurrence of human cerebellar serotonin 5-HT(2A) receptors (5-HT(2A)R) is equivocal and their status in schizophrenia unknown. Using a range of techniques, we investigated cerebellar 5-HT(2A)R expression in 16 healthy subjects and 16 subjects with schizophrenia. Immunocytochemistry with a monoclonal antibody showed labelling of Purkinje cell bodies and dendrites, as well as putative astrocytes. Western blots showed a major band at approximately 45 kDa. Receptor autoradiography and homogenate binding with [(3)H]ketanserin revealed cerebellar 5-HT(2A)R binding sites present at levels approximately a third of that in prefrontal cortex. 5-HT(2A)R mRNA was detected by reverse transcriptase-polymerase chain reaction, with higher relative levels in men than women. Several aspects of 5-HT(2A)R expression were altered in schizophrenia. 5-HT(2A)R immunoreactivity in Purkinje cells was partially redistributed from soma to dendrites and was increased in white matter. 5-HT(2A)R mRNA was decreased in the male patients. 5-HT(2A)R measured by dot blots and [(3)H]ketanserin binding (B(max) and K(d)) were not significantly altered in schizophrenia. These data show that 5-HT(2A)R gene products (mRNA, protein, binding sites) are expressed in the human cerebellum at nonnegligible levels; this bears upon 5-HT(2A)R imaging studies which use the cerebellum as a reference region. 5-HT(2A)R expression is altered in schizophrenia; the shift of 5-HT(2A)R from soma to dendrites is noteworthy since atypical antipsychotics have the opposite effect. Finally, the results emphasise that expression of a receptor gene is a mutifaceted process. Measurement of multiple parameters is necessary to give a clear picture of the normal situation and to show the profile of alterations in a disease.